APLIKASI KESEHATAN DAN KESELAMATAN KERJA PERKANTORAN, ADMINISTRASI, DAN TEKNOLOGI INFORMASI (Literatur Review) - Luluk Mamlu Atun; M. Safari Ihwan Sani; Yunita; Slamet Mardiyanto Rahayu (Nusadaya Journal of Multidiciplinary Studies, 2023)
Occupational Health and Safety (K3) Office is part of the overall office building management system in order to control risks related to work activities in order to create a comfortable and efficient workplace.